Land pressures, the evolution of farming systems, and development strategies in Africa: A synthesis - Jayne, Thomas S.; Chamberlin, Jordan; Headey, Derek D. (Elsevier, 2014)
Evidence assembled in this special issue of Food Policy shows that rising rural population densities in parts of Africa are profoundly affecting farming systems and the region’s economies in ways that are underappreciated in current discourse on African development issues. This study synthesizes how people, markets and governments are responding to rising land pressures in Africa, drawing on key findings from the various contributions in this special issue. The papers herein revisit the issue of Boserupian agricultural intensification as an important response to land constraints, but they also go further than Boserup and her followers to explore broader responses to land constraints, including non-farm diversification, migration, and reduced fertility rates. Agricultural and rural development strategies in the region will need to more fully anticipate the implications of Africa’s rapidly changing land and demographic situation, and the immense challenges that mounting land pressures pose in the context of current evidence of unsustainable agricultural intensification, a rapidly rising labor force associated with the region’s current demographic conditions, and limited nonfarm job creation. These challenges are manageable but will require explicit policy actions to address the unique development challenges in densely populated rural areas.